Long-Term Drying Shrinkage Strain of Engineered Cementitious Composite Concrete Contains Polymeric Fibers - Ikram Faraoun Al-Mulla; Abbas Salim Al-Ameeri; Tareq Salih Al-Attar (Journal of Engineering)
The lack of concrete tensile stress endurance led to the invention of engineered cementitious composite. However, the absence of gravel from the mixture in addition to the high binder content may lead to high shrinkage strain. Therefore, a radical solution to this problem is worth to be anticipated. The importance of this research lies in investigating the long-term drying shrinkage strain of the engineered cementitious composite since there is a lack of information regarding this behavior. Mixes of 30 and 60 MPa strengths were produced with polyvinyl alcohol fibers PVA-ECC and polypropylene fibers PP-ECC. The drying shrinkage strain of PVA-ECC mixes has been compared to PP-ECC mixes for both short term (0–28 days) and long term (0–360 days). Results indicated that all PVA-ECC mixes exhibited lower drying shrinkage strains than PP-ECC mixes. The ultimate drying shrinkage strain was recorded to be 1200 microstrain at 28 days. The increment in drying shrinkage strain after 28 days was 5.6% in PVA-ECC mixes when compared to that in PP-ECC mixes which was 6.77%. For high strength levels, the drying shrinkage strain at the age of 360 days declared a reduction of 3.5% for PVA-ECC compared to PP-ECC mixes. Also, it was lower for mixes with 60 MPa (6.3%) than for mixes with 30 MPa (7.6%). Therefore, despite the higher cement content for mixes with 60 MPa strength, the higher fiber volume fraction and the higher PVA solution percentage restricted the drying shrinkage strain increment. The research also addresses some mechanical tests of engineered cementitious composite concrete such as compressive strength, flexural strength, and strain capacity that may provide a strong relation to the drying shrinkage behavior of the different mixes. The scanning electron microscope images were involved in this research to declare the impact of fiber types on the microstructure of the ECC mixes.